Components of contraceptive counselling postpartum women receive during antenatal and postnatal health care services: A qualitative approach - Desmond Klu (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2019)
Contraceptive counselling is seen as a major part of public health care, maternal and child health care. Therefore, antenatal and postnatal periods are regarded as the appropriate opportunities for women to receive education on contraceptives. However, not much attention has been given to the contents, materials used and frequency of the contraceptive education women receive as this is critical in understanding the contraceptive behaviour of these women. Against this backdrop, this study explores the components of contraceptive counselling postpartum women receive when they attend antenatal and postnatal health care services in order to provide insights into the various contraceptive counselling given to postpartum women who attend antenatal and postnatal clinics.